An Assessment Of Metal Distribution And Metal Soluble Fractions In The Edible Molluscs From Malaysia - Edward Thomas, Franklin Berandah (2009)

(untitled)
The present study focused on the heavy metal concentrations in the different parts of 12 species of Malaysian molluscs, six species of bivalves and gastropods, respectively. The aim of the present study was to provide information on the concentrations of the essential metals: Cu, Fe and Zn and the non-essential metals: Cd, Ni and Pb in the edible tissues of molluscs with particular reference to the food safety and ecotoxicological points of views. For bivalves, Cu, Fe and Zn concentrations in the edible parts ranged at 1.80-79.8 μg/g dw, 42.9-4895 μg/g dw and 28.3-379 μg/g dw, respectively. While for Cd, Pb and Ni, they ranged at 0.253-22.4 μg/g dw, 0.558-46.5 μg/g dw and 0.656-23.6 μg/g dw, respectively. As for gastropods, Cu, Fe and Zn concentrations in the edible parts ranged at 1.97-686 μg/g dw, 51.2-2921 μg/g dw, 22.8-337 μg/g dw, respectively. While for Cd, Pb and Ni, they ranged at 0.159-32.9 μg/g dw, 1.20-43.0 μg/g dw and 0.222-27.9 μg/g dw, respectively. The study on the soluble and insoluble heavy metal fractions revealed that an abundance of soluble metals like Cd, Pb and Ni were consistently found in some tissues of the molluscs such as in the foot, mantle and muscle and they could potentially be transferred through the food web (predators). The total metal concentrations in the different parts were compared with the food permissible limits set by six organizations around the world. However, to overcome the overestimation of food safety based on the total metal concentrations in the different edible tissues, determination of the metal soluble fractions in the tissues were further investigated in this study. The soluble concentrations were compared with the permissible limits set by the Environmental health Criteria (1998, 2001) and the FAO/WHO (1984). From the present findings, it was found that consumption of large amounts of Per. viridis, G. expansa and most of the gastropods could pose metal toxic to their consumer. The elevated of Cu and Zn concentrations in most of the edible parts of the gastropods suggested that the consumption of large amounts of most gastropods were not advisable. As for Cd levels, it was found that the byssus of Per. viridis and D. faba; and the digestive gland and mantle of Chi. capucinus were not safe for continuous consumption (for example: more than a week) since the levels would exceed the permissible limit. Besides, the continuous consumption of the byssus of Per. viridis and D. faba would also potentially cause Pb toxicity. The information on the metal distributions in the different parts obtained by using the cluster analysis is important to facilitate the biomonitoring of the marine environment, which based on the use of different tissues in the species of molluscs of Malaysia